TEACHING AT THE RIGHT LEVEL (TaRL) THROUGH THE ALL SMART CHILDREN APPROACH (SAC) IMPROVES STUDENT'S LITERATURE ABILITY - Lalu Jazuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
The TaRL approach was developed by Pratham. In his video entitled How to Teach Kids to Read in as Little as 50 Days he says: “All over the world a growing belief is that if you open a school the children will (successfully) learn. But children are not studying, for example in India 97% are enrolled in schools but 50% of children cannot read paragraphs for 2nd graders”. The stages in the implementation of SAC consist of 3 stages: assessment, grouping, and learning according to level/ability. After going through these three stages by carrying out literacy learning for 2 weeks, then a reassessment is carried out. The results of the SAC program assessment can improve children's abilities, namely at the beginner level, letters, words, and paragraphs decreased from 55% to 50%, and at the story level increased from 45% to 50%. The students who progressed to level up reached 30%. The data on increasing students' literacy skills were obtained using the Naturalistic Research method. Grade 1 to grade 6 children are assessed individually. The instrument used is a test. The tests used are letter cards, word cards, paragraph texts, and short story texts equipped with questions about the content of the story.